Validation of the brief resilience scale in adolescents and its mediating role between indirect violence, PTSD, and substance use - Nuño-Gutiérrez, Bertha Lidia (Acta Universitaria, 2026)
Resilience is a dynamic personality characteristic that enables adaptation in the face of adversity. There is substantial scientific evidence demonstrating its association with mental health, highlighting the importance of its study and measurement. The brief resilience scale (EBRA-14) is one of the most widely used instruments internationally. Therefore, the aim of this study was to obtain evidence of the validity and reliability of the EBRA-14, as well as to evaluate its mediating role between exposure to indirect violence, post-traumatic stress disorder symptoms, and substance use. A questionnaire was administered to 744 upper-secondary students in Guadalajara, Jalisco, Mexico. Results showed adequate levels of validity and reliability in the two factors of the scale, with eight items grouped into two dimensions, consistent with the original version. Furthermore, resilience was confirmed to mitigate the negative impact of exposure to violence on substance use.